Exploration Of Bird Species Diversity In Sanggabuana Area, Citalaksana, Karawang, West Java - Wotrunnada, Ananda; Agustin, Dini; Putri, Maharani Joana; Friscilla, Sulastri; Ramadhine, Teghes Diva; Azriel, Muhamad; Assalam, Muhammad Hudan (Journal of Tropical Biodiversity, 2025)
Mount Sanggabuana with an altitude of 1,074 above the sea level has an exciting and high biodiversity. Still, currently, its status is being sought to officially become a National Park and not many research reports have been found that discuss birds in the area. The purpose of this paper is to determine the diversity of bird species in the Sanggabuana Area, Cintalaksana, Tegalwaru, Karawang, West Java. The research was conducted on 15-17 August 2024 using the point count method. Based on the results of observations, 26 bird species from 16 families were recorded and there are five bird species protected according to the Minister of Environment and Forestry Regulation No. 20 of 2018, one of which is the bido snake eagle (Spilornis cheela) from the Accipitridae. The diversity of bird species in the Sanggabuana area is classified in the medium category, details of the H' value in the primary forest (Jalur Hutan) of 2.54 and in the secondary forest (Jalur Curug) of 2.55. The dominating bird species in the primary forest habitat is Takur tohtor (Psilopogon armillaris) while in the secondary forest is Cucak kutilang (Pycnonotus aurigaster).